Interactive Effects of Ambient Temperature and Light Sources at High Relative Humidity on Growth Performance and Blood Physiological Variables in Broilers Grown to 42 Day of Age - Olanrewaju , Hammed A.; Purswell, Joseph L.; Collier, Stephanie D.; Branton, Scott L. (International Journal of Poultry Science, 2016)
Objective: The objective of the study is to evaluate the interactive effects of ambient temperature and light sources at high relative humidity on growth performance and blood physiological reactions in broilers grown to 42 days of age. Methodology: The experiment consisted of two levels (Moderate = 21.1°C and high = 26.7°C) of temperatures and two light sources (ICD and PSF-LED) at high relative humidity (80%). A total of 532 1 day-old Ross 708 chicks were randomly distributed into 8 environmentally-controlled rooms (22 males and 22 females chicks per room). Feed and water were provided ad libitum. Light treatment started from 1 day, while temperature and RH were applied continuously from 22 days through 42 days. Both feed intake and bird’s weight were recorded on 1 and 21day (before initiation of the treatments), 28 and 42 day for the growth performance. Also, wing brachial vein blood (3 mL) samples were collected on weigh days from six (3 males/3 females) randomly selected chicks from each room. Results: Treatments with only high ambient temperature significantly (p<0.05) reduced Body Weight (BW), Body Weight Gain (BWG) and Feed Intake (FI), but no treatments effect were observed for Feed Conversion Ratio (FCR) and mortality. Also, there was no effect of light sources and high humidity on all examined production variables. In addition, only treatments with high ambient temperature significantly (p<0.05) increased Hb, Hct, McHc and Osmo along with significantly (p<0.05) reduced Na+. However, light sources and high humidity had no effect on all examined blood physiological variables. All acid-base changes during these combined treatments were still within the normal acid-base homeostasis and physiological ranges. Plasma corticosterone concentrations were not affected by treatments. Conclusion: It was concluded that the LED sources evaluated in this study may be suitable for replacement of ICD light source in commercial poultry facilities along with moderate temperature with or without high relative humidity to reduce energy cost and optimize production efficiency without compromising the welfare of broilers.